GC-TOF/MS-based metabolomics analysis to investigate the changes driven by N-Acetylcysteine in the plant-pathogen Xanthomonas citri subsp. citri - Simone Cristina Picchi (Nature Portfolio, 2021)
Abstract N-Acetylcysteine (NAC) is an antioxidant, anti-adhesive, and antimicrobial compound. Even though there is much information regarding the role of NAC as an antioxidant and anti-adhesive agent, little is known about its antimicrobial activity. In order to assess its mode of action in bacterial cells, we investigated the metabolic responses triggered by NAC at neutral pH. As a model organism, we chose the Gram-negative plant pathogen Xanthomonas citri subsp. citri (X. citri), the causal agent of citrus canker disease, due to the potential use of NAC as a sustainable molecule against phytopathogens dissemination in citrus cultivated areas. In presence of NAC, cell proliferation was affected after 4 h, but damages to the cell membrane were observed only after 24 h. Targeted metabolite profiling analysis using GC–MS/TOF unravelled that NAC seems to be metabolized by the cells affecting cysteine metabolism. Intriguingly, glutamine, a marker for nitrogen status, was not detected among the cells treated with NAC. The absence of glutamine was followed by a decrease in the levels of the majority of the proteinogenic amino acids, suggesting that the reduced availability of amino acids affect protein synthesis and consequently cell proliferation.